Don't look now - Du Maurier, Daphne 1907-1989; Donaggio, Pino 1941- (<<The>> Criterion Collection, 2015)
"Donald Sutherland and Julie Christie mesmerize as a married couple on an extended trip to Venice following a family tragedy. While in that elegantly decaying city, they have a series of inexplicable, terrifying, and increasingly dangerous experiences. A masterpiece from Nicolas Roeg, DonĐt Look Now, adapted from a story by Daphne du Maurier, is a brilliantly disturbing tale of the supernatural, as renowned for its innovative editing and haunting cinematography as its naturalistic eroticism and unforgettable climax and denouement, one of the great endings in horror history." [criterion.de]
Aspect ratio 1.85:1. - New 4K digital restoration
Orig.: Großbritannien, Italien 1973
Enth. new conversation between editor Graeme Clifford and film writer and historian Bobbie O'Steen ; "Don't look bow," Looking Back, a short 2002 documentary featuring Roeg, Clifford, and cinematographer Anthony Richmond ; "Death in Venice", a 2006 interview with composer Pino Donaggio ; "Something interesting", a new piece on the writing and making of the film, featuring recent interviews with Richmond, actors Julie Christie and Donald Sutherland, and coscreenwriter Allan Scott ; "Nicolas Roeg: the enigma of Film", a new piece on Roeg's style, featuring recent interviews with filmmakers Danny Boyle and Steven Soderbergh ; Q&A with Roeg from 2003 at London's Ciné Lumière ; trailer ; an essay by film critic David Thompson